Estimation of genetic parameters of litter weights of Khari goats and their response towards different non-genetic factors under low input management system in Nawalparasi, Nepal - Bhattarai, N.; Kolachhapati, M. R.; Devkota, N. R.; Thakur, U. C.; Neopane, S. P. (Journal of the Institute of Agriculture and Animal Science, 2018)
Accurate estimates of genetic parameters are important for genetic improvement in Khari goats. In this regard, altogether 1005 adult does of Khari goat in Deurali VDC, Nawalparasi were evaluated in terms of litter weight at birth (LWB) and litter weight at weaning (LWW) and their genetic parameters from February, 2012 to January 2015. Least square means (LSM) and standard errors of the mean (SEM) for these traits were determined with respect to some non-genetic factors such as altitude, season of conception, season of kidding, dam’s parity, dam’s size at conception, and birth type. Accordingly, Overall LSM±SE of LWB and LWW in present study were determined 3.97±0.06 and 18.21±0.34 Kgs., respectively. Where, LWB did not differed significantly with altitude and dam’s parity, however, it was significantly influenced (p<0.001) by the season of conception, season of kidding, dam’s size at conception, and birth type. Similarly, LWW was significantly varied with respect to altitude (p<0.01), season of conception (<0.001), season of kidding (<0.05), dam’s parity (<0.001), dam’s size at conception (<0.001), and birth type (<0.001). Moderately high heritability estimates of LWB (0.52±0.16) and LWW (0.56±0.17) indicated that these traits were under the strong influence of additive genes and selection based the superiority of individual doe would be appropriate for successful genetic improvement. Highly significant positive genetic (rA=0.95) and phenotypic correlation (rP=0.91) between LWB and LWW suggested that selection for any of these trait would result in considerable positive change in other trait. More specifically, LWB can be used as a guide to select replacement does targeting to increased LWW within the herd. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 251-258